Remote Limb Ischemic Postconditioning Protects Against Ischemic Stroke by Promoting Regulatory T Cells Thriving - Hai‐Han Yu (Wiley, 2021)
Background Remote limb ischemic postconditioning (RLIPoC) has been demonstrated to protect against ischemic stroke. However, the underlying mechanisms of RLIPoC mediating cross‐organ protection remain to be fully elucidated. Methods and Results Ischemic stroke was induced by middle cerebral artery occlusion for 60 minutes. RLIPoC was performed with 3 cycles of 10‐minute ischemia followed by 10‐minute reperfusion of the bilateral femoral arteries immediately after middle cerebral artery reperfusion. The percentage of regulatory T cells (Tregs) in the spleen, blood, and brain was detected using flow cytometry, and the number of Tregs in the ischemic hemisphere was counted using transgenic mice with an enhanced green fluorescent protein‐tagged Foxp3. Furthermore, the metabolic status was monitored dynamically using a multispectral optical imaging system. The Tregs were conditionally depleted in the depletion of Treg transgenic mice after the injection of the diphtheria toxin. The inflammatory response and neuronal apoptosis were investigated using immunofluorescent staining. Infarct volume and neurological deficits were evaluated using magnetic resonance imaging and the modified neurological severity score, respectively. The results showed that RLIPoC substantially reduced infarct volume, improved neurological function, and significantly increased Tregs in the spleen, blood, and ischemic hemisphere after middle cerebral artery occlusion. RLIPoC was followed by subsequent alteration in metabolites, such as flavin adenine dinucleotide and nicotinamide adenine dinucleotide hydrate, both in RLIPoC‐conducted local tissues and circulating blood. Furthermore, nicotinamide adenine dinucleotide hydrate can mimic RLIPoC in increasing Tregs. Conversely, the depletion of Tregs using depletion of Treg mice compromised the neuroprotective effects conferred by RLIPoC. Conclusions RLIPoC protects against ischemic brain injury, at least in part by activating and maintaining the Tregs through the nicotinamide adenine dinucleotide/nicotinamide adenine dinucleotide hydrate pathway.